Adenoidal-Nasopharyngeal Ratio in Healthy Adults on Cone Beam Computed Tomography. Issue 5 (21st September 2022) - Chan, King Chong; Vasilyeva, Daria; Bansal, Tarika; Moonis, Gul
Abstract : Objective: This study aimed to quantify the adenoidal-nasopharyngeal ratio (ANR) in a cohort of healthy adults on cone beam computed tomography (CT) using the Fujioka method, which is a reproducible measure of adenoid size and nasopharyngeal patency. Methods: Electronic health records and maxillofacial cone beam CT in 202 consecutive patients aged 16 years and older were retrospectively reviewed. Patients with a history of adenoidectomy, sinonasal disease, lymphoproliferative disorders, and cleft palate were excluded from the study. The midsagittal reconstructed cone beam CT image was used to determine the ANR. Statistical analysis was conducted using 1-way analysis of variance. Results: Of the 202 subjects, 131 were female and 71 were male. The mean ± SD subject age was 45.43 ± 20.79 years (range, 16–91 years). The mean ± SD ANR in all subjects was 0.22 ± 0.13 (range, 0.03–0.75) and in each decade of adult life was as follows: younger than 21 years, 0.39 ± 0.12; 21 to 30 years, 0.29 ± 0.11; 31 to 40 years, 0.21 ± 0.09; 41 to 50 years, 0.20 ± 0.07; 51 to 60 years, 0.16 ± 0.10; 61 to 70 years, 0.13 ± 0.05; 71 to 80 years, 0.12 ± 0.05; 81 to 90 years, 0.11 ± 0.04; and 91 years or older, 0.10 ± 0. The differences in mean ANR among the age subgroups were statistically significant ( P < 0.001). Conclusions: The mean ANR gradually decreased from 0.39 in the second decade of life to 0.16 in the sixth decade of life and plateaued at approximately 0.10 thereafter.